Differential Diagnostics of Wilson disease - article Editorial (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To present modern methods of diagnostics, treatment and monitoring of patients with Wilson disease (WD).Original positions. Diagnosis of Wilson disease should be excluded at each patient with liver disease of non-specified etiology at the age of 3 to 55 years. Dramatic decrease of ceruloplasmin level (CP) in blood serum (less than 50 mg /l or less 5 mg/dl) should be regarded as the convincing proof for the benefit of WD diagnosis. At moderate or subnormal values of this parameter it is necessary to carry out further tests . Normal CP level cannot exclude WD diagnosis. To specify the diagnosis investigation of copper metabolism is required. Evaluation of neurologic status and radiological study of the brain (preferably – magnetic-resonance) should be done prior to onset of treatment in all patients with neurologic form of WD, radiological methods serve for differential diagnostics purpose. Genetic analysis is expedient at diagnostic difficulties. At each patient with acute liver failure and negative Coombs test for intravascular hemolysis, moderate elevation of serum aminotransferases activity or decreased level of alkaline phosphatase WD should be excluded. Primary treatment of patients with clinical symptomatology should include chelating agent (DPenicillaminum or trientine). It is necessary to avoid the use of food products and water with high contents of copper, especially in the first year of treatment. Treatment of presymptomatic patients or patients at maintenance therapy can be carried out with the help of chelator or Zinc. The acute liver failure caused by WD, serves as the indication for immediate liver transplantation. Patients with decompensated cirrhosis, tolerant to chelator therapy, should be regarded as candidates for transplantation. During pregnancy WD treatment proceeds, but by the lower doses of copper chelators. Conclusion. Wilson disease – is one of the first diseases of liver for which effective method of treatment has been found. WD was a fatal disease before methods of its treatment have been developed 50 years ago. Discovering and introduction of D-Penicillamine in clinical practice revolutionized WD treatment. The most effective method, allowing to keep life to the patient, is orthotopic transplantation of the liver.